Qualidade de vida de famílias que têm filhos com deficiência intelectual leve associada ao transtorno do espectro do autismo leve - Borilli, Marcela Cesaretti (2020)
Introduction: Intellectual Disability (ID) and Autism Spectrum Disorder (ASD) are often concomitant childhood developmental disorders, which impact on the dynamic and the family quality of life. Objectives: This research assessed the impact of mild ID associated with mild ASD in the family quality of life (FQoL). Methods: This is cross-sectional and descriptive research that analyzed 69 families with children with mild ID and ASD, confirmed by WISC-IV and CARS, respectively, ranging from 6 to 16 years old (9.5±2.6). Data were collected by conducting face-to-face questionnaires including sociodemographic and clinical information, the functional Barthel and Lawton & Brody indexes and the Beach Center FQoL Scale. For statistical analysis, parametric tests were used (t test, ANOVA, Pearson and Spearman linear correlations, and linear regression), considering that the dependent variable (FQoL) showed a normal distribution. A significance level of 5% was adopted. Results: The people with ID and ASD had an average score of 88.19±11.53 in the Barthel index, indicating moderate dependence on basic activities of daily living; and had an average score of 2.13±0.89 in the Lawton & Brody index, indicating severe dependence in the instrumental activities of daily living. The total FQoL average score (3.561±0.337) was lower than the scores of the “family interaction” (3.908±0.420; p<0.001), “parenting” (3.785±0.348; p<0.001) and “disability-related support” (3.975±0.161; p<0,001) domains, and higher than the scores of the “physical/material well-being” (3.194±0.642; p<0.001) and “emotional well-being” (2.750±0.620; p<0.001) domains. The multiple correlation showed that the parents’ marital condition, monthly family income, family religious practice and effective communication skills among the individual with ID and ASD were predictors of the FQoL (R2=0.407; p<0.001). Conclusions: The FQoL was negatively impacted by emotional well-being and physical and material conditions. We suggest adopting measures to improve these two dimensions of FQoL and reducing family burden in the care of children with ID and ASD. The FQoL also may be improved through actions that encourage effective communication of children with ID and ASD. These results may contribute for building a full support services care for patients with ID and ASD, and their families, in the Brazilian Unified Health System.